Key learning outcomes for clinical pharmacology and therapeutics education in Europe: A modified Delphi study. - David J. Brinkman; Jelle Tichelaar; Lidwine B. Mokkink; Thierry Christiaens; Robert Likic; Romaldas Maciulaitis; Joao Costa; Emilio J. Sanz; Simon R. Maxwell; Milan C. Richir; Michiel A. van Agtmael (Wiley, 2022)
Harmonizing clinical pharmacology and therapeutics (CPT) education in Europe is necessary to ensure that the prescribing competency of future doctors is of an uniform high standard. As there are currently no uniform requirements, our aim was to achieve consensus on key learning outcomes for undergraduate CPT education in Europe. We used a modified Delphi method consisting of three questionnaire rounds and a panel meeting. 129 experts from 27 European countries were asked to rate 307 learning outcomes. 92 experts (71%) completed all three questionnaire rounds, and 33 experts (26%) attended the meeting. 232 learning outcomes from the original list, 15 newly suggested and 5 rephrased outcomes were included. These 252 learning outcomes should be included in undergraduate CPT curricula to ensure that European graduates are able to prescribe safely and effectively. We provide a blueprint of a European core curriculum describing when and how the learning outcomes might be acquired. This article is protected by copyright. All rights reserved.